2022
DOI: 10.52142/omujecm.39.2.19
|View full text |Cite
|
Sign up to set email alerts
|

Effect of complete blood count parameters on the clinical course of COVID-19 in pregnant women

Abstract: Coronavirus Disease-19 (COVID-19) pandemic, affected pregnant women as well as many people. Aim of this study is to compare complete blood count (CBC) parameters of pregnant women infected with COVID-19 to that of healthy pregnant women and determine their prognostic features. 142 pregnant women infected with COVID-19 and 46 healthy pregnant women, included in this retrospective case-control study. Patients infected with COVID-19 were grouped as mild, moderate and severe, according to the findings of oxygen sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The NLR value can be a prognostic biomarker and was reported in various studies including patients with non-severe, mild and severe Covid-19 infections (22,23). In addition, a meta-analysis showed that individuals with severe Covid-19 have a higher NLR than nonsevere ones (24) (28). However, the NLR value showed significant differences when evaluated according to disease severity (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLR value can be a prognostic biomarker and was reported in various studies including patients with non-severe, mild and severe Covid-19 infections (22,23). In addition, a meta-analysis showed that individuals with severe Covid-19 have a higher NLR than nonsevere ones (24) (28). However, the NLR value showed significant differences when evaluated according to disease severity (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis showed that individuals with severe Covid-19 have a higher NLR than nonsevere ones (24) (28). However, the NLR value showed significant differences when evaluated according to disease severity (28,29). On the other hand, a retrospective analysis of a large cohort revealed that the NLR values in the first, second and third trimesters of pregnancy may vary (30).…”
Section: Discussionmentioning
confidence: 99%